(untitled) (Bangladesh Journal of Agricultural Research, 2018)
Compost tea, Tilt 250 EC and Bavistin 50 WP were evaluated for controlling brown spot and narrow brown spot diseases of rice in the field laboratory of the Department of Plant Pathology, Bangladesh Agricultural University, Mymensingh during the period from July to December, 2011. Significant effect of different treatments was observed on the severity of brown spot and narrow brown spot of rice as compared to control. The results evidently showed the lowest brown spot severity in T4 (Tilt 250 EC applied as foliar spray) which was statistically similar to T3 (Compost tea as soil drenching) while the highest severity was recorded in untreated control plot at booting and ripening stage. But narrow brown spot severity was lowest in T4 (Tilt 250 EC as foliar spray) which was similar to T5 (Tilt 250 EC as soil drenching), T6 (Bavistin 50 WP as foliar spray) and highest severity was found in T2 (Compost tea as foliar spray) which was statistically similar to T1 (control), T3 (Compost tea as soil drenching), T7 (Bavistin 50 WP as soil drenching) at booting stage. But at ripening stage the highest severity was found in T1 (control) and the lowest severity was found in T4 (Tilt 250 EC as foliar spray) which was statistically similar to T5 (Tilt 250 EC as soil drenching). However, soil drenching and foliar application of compost tea performed better as compared to control in reducing the severity of brown spot. But compost tea as foliar spray increased the narrow brown spot disease. Significant effect of the treatments was observed on growth and yield contributing characters except panicle length. Foliar and soil application of Tilt and soil application of compost tea showed better performance in increasing growth and yield contributing characters as compared to all other treatments. Bangladesh J. Agril. Res. 42(4): 621-629, December 2017